Antioxidant potential of Fragrea acuminatissima Merr. by different extraction techniques - Nurul Amira Buslima; Mohammad Afiq Faiz Shaharudin; Tang, Bee Eik; Shamsul Mohamad (2016)
Developing countries are still counting on herbal medicine which aims to promote primary health care with better cultural, human acceptability and fewer side effects. Fragrea acuminatissima is one of underutilized herb consumed by Temiar tribe in Malaysia which able to give the similar beneﬁts. The most important attribute in developing herbal based product is the extraction condition and selection of the technique used will potentially affect the expression of antioxidant compound in herbal plant. Technical problem arising from the extraction phase also urge the needs to elucidate the best techniques for respective herbal product. Therefore, this study was aimed to investigate the best extraction techniques (maceration, orbital shaker assisted, ultrasonic assisted and microwave assisted) on Total Phenolic Content (TPC). Total Flavonoid Content (TFC) and antioxidant activity of F. acuminatissima stem and root parts by using methanol solvent. Folin-Ciocalteu method was used for determination of TPC, aluminium chloride colorimetric method for TFC, while antioxidant activity was determined by DPPH radical scavenging assay. Overall, the best extraction method of F. acuminatissima was ultrasonic assisted extraction which exhibited the highest percentage yield, TPC and TFC values for both plant parts. Based on the DPPH assay, F. acuminatissima have procured the excellent lC₅₀ of 29.954 μg/ml by ultrasonic assisted extraction for stem while maceration techniques showed the best IC₅₀ for root at 76.996 μg/ml. Positive moderate and strong correlation between TPC, TFC and DPPH was detected which support the result obtained. ln brief, ultrasonic assisted technique was suggested to be used in future research of this plant for phytochemical proﬁling, bioactivity assays and herbal product development.